2012
DOI: 10.1371/journal.pone.0040804
|View full text |Cite
|
Sign up to set email alerts
|

No Influence of Dabigatran Anticoagulation on Hemorrhagic Transformation in an Experimental Model of Ischemic Stroke

Abstract: BackgroundDabigatran etexilate (DE) is a new oral direct thrombin inhibitor. Clinical trials point towards a favourable risk-to-benefit profile of DE compared to warfarin. In this study, we evaluated whether hemorrhagic transformation (HT) occurs after experimental stroke under DE treatment as we have shown for warfarin.Methods44 male C57BL/6 mice were pretreated orally with 37.5 mg/kg DE, 75 mg/kg DE or saline and diluted thrombin time (dTT) and DE plasma concentrations were monitored. Ischemic stroke was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…In experimental models of ischemic stroke, neither dabigatran pretreatment nor continued administration of dabigatran after stroke onset significantly increased the risk or volume of hemorrhagic transformation after middle cerebral artery occlusion. 95,96 Clinical data are anecdotal only. The phase III trials establishing the role of NOACs for stroke prevention in NVAF excluded patients within 7 to 30 days of stroke.…”
Section: Management Of Patients On Noacs Who Are At Risk For Bleedingmentioning
confidence: 99%
“…In experimental models of ischemic stroke, neither dabigatran pretreatment nor continued administration of dabigatran after stroke onset significantly increased the risk or volume of hemorrhagic transformation after middle cerebral artery occlusion. 95,96 Clinical data are anecdotal only. The phase III trials establishing the role of NOACs for stroke prevention in NVAF excluded patients within 7 to 30 days of stroke.…”
Section: Management Of Patients On Noacs Who Are At Risk For Bleedingmentioning
confidence: 99%
“…The same group reported similar results after treatment of experimental animals with dabigatran [ 13 ]. On the other hand, dabigatran did not significantly increase hemorrhagic transformation after transient focal cerebral ischemia in mice [ 14 ] or risk of secondary hemorrhages after thrombolysis in various rodent models of ischemia and reperfusion [ 10 ] or collagenase-induced intracranial hemorrhage [ 11 ]. We and others reported that warfarin and dabigatran both induce glomerular hemorrhage in the kidney [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…All rats were anesthetized with a mixture of nitrous oxide/oxygen/isoflurane (69%:30%:1%) during surgical preparation with an inhalation mask. Focal cerebral ischemia and ET was induced using the tMCAO model as described previously 11 , 32 , 33 . The rats’ body temperature was monitored and maintained at 37.0 ± 0.5 °C by a heating pad during the surgical procedure.…”
Section: Methodsmentioning
confidence: 99%